Cloud Accounting : The Development of Accounting Information System in Industry 4.0 in Indonesia - Salem, Sumini; Nurdayadi, Nurdayadi; Alfiandri, Alfiandri (Conference Series, 2021)
The digitalization era of Industry 4.0 in Indonesia has significance roles in business sectors and accountancy in which they are progressing and developing. Future accountants are expected to equip upgraded-skills due to the globalization and digitalization of Industry 4.0. The trend of emergence technologies in accounting information system is Cloud Accounting. Hence, the digital transformation of the accounting information system is important for accountants to be fully aware that traditional accounting system will be gradually replaced to more digitalized accounting system. This paper focuses on the needs of Cloud Accounting and the extent of the development of accounting information system in Industry 4.0 in Indonesia. The research methodology of the study is qualitative analysis. Interview, questionnaire and focus group discussion were conducted to gather information from views of accounting business providers, practitioners, and accountants. Published journals of related topic were also examined to get viewpoints of the researchers. The results show that 90% of the respondents agree that accounting information system has evolved to more digitalized accounting system in Industry 4.0. Future accountants will have more challenging accountancy roles due to the digitalization on accounting information system in which digitalized accounting information system will take over with the advancement of technology through education and higher education should prepare future accountants by knowledge of Cloud Accounting in the curriculum of accounting study program.